What is the fundamental theorem of algebra for x^6-64?

1 answer

I would understand it to say that
x^6 - 64 = 0 has 6 roots

Proof:
first treat x^6 as a difference of squares
x^6 - 64
= (x^3 - 8)(x^3 + 8)
now as a difference of cubes for the first factor, and a sum of cubes for the second part
= (x-2)(x^2 + 2x + 4)(x+2)(x^2 - 2x + 4)

so x^6 - 64 = 0
(x-2)(x^2 + 2x + 4)(x+2)(x^2 - 2x + 4) = 0

x-2=0 ----> x=2
x+2=0 ----> x=-2
x^2+2x+4)=0 ---> x = (-2 ± √-12)/2 = -1 ± √3 i
x^2 - 2x + 4=0 --> x = (2 ± √-12)/2 = 1 ± √3 i

6 roots!
Similar Questions
  1. The Fundamental Theorem of Algebra Quick Check3 of 53 of 5 Items Question Apply the Fundamental Theorem of Algebra to determine
    1. answers icon 1 answer
  2. The Fundamental Theorem of Algebra Quick Check1 of 51 of 5 Items Question Show that the Fundamental Theorem of Algebra is true
    1. answers icon 1 answer
  3. The Fundamental Theorem of Algebra Quick Check2 of 52 of 5 Items Question Without solving, apply the Fundamental Theorem of
    1. answers icon 1 answer
    1. answers icon 0 answers
more similar questions